Barron's profiles of American colleges (Latest data on more than 1500 schools): Description of the colleges (Barron's Educational Series, 1992)
The book describes in detail the more than 1550 colleges. The college profiles are presented alphabetically by state, and the states are also arranged in alphabetical order. Maps of the state begin each chapter. Actually, this book covers more than the fifty states; it also describes colleges in the District of Columbia, Guam, Puerto Rico, the Virgin Island, and foreign countries